Collusion Over the Business Cycle - Kyle Bagwell; Robert W. Staiger (Northwestern University, Kellogg School of Management, Center for Mathematical Studies in Economics and Management Science, 1995)
We present a theory of collusive pricing in markets subject to business cycle fluctuations. In the business cycle model that we adopt, market demand alternates stochastically between fast-growth (boom) and slow-growth (recession) phases. We provide a complete characterization of the most-collusive prices and show that: (1). the most-collusive prices may be procyclical (countercyclical) when demand growth rates are postively (negatively) correlated through time, and (2). the amplitude of the collusive pricing cycle is larger when the expected duration of boom phases decreases and when the expected duration of recession phases increases. We also offer a generalization of Rotemberg and Saloner's (1986) model, and interpret their findings in terms of transitory demand shocks that occur within broader business cycle phases.
Keywords: 330